Sociology of the new media environment in the western post-truth society - F. I. Sharkov; V. V. Silkin; O. F. Kireeva (RUDN journal of Sociology)
The new media presents forms of communication that facilitate production, distribution and exchange of content on platforms and networks that enable interaction and collaboration. Over the past three decades, the new media has developed rapidly and continues to develop in new, previously unknown ways, providing greater opportunities for social governance and political practice. With their convergent properties, the new media has changed the ways in which government institutions operate and political leaders communicate. The new media environment has significantly transformed the system of social communications and changed the role of journalists in political processes. Today digital platforms used by the media provide the electoral system with new ways of interacting with the electorate, introducing new ways for holding elections and in general expanding mechanisms of civil participation. At the same time, the new media in the post-truth society has become the main source of information, which presents lies supplemented by individual facts as news. The dubious quality of such news creates serious problems for the democratic discourse. In the emerging era of post-truth, the new media strengthens negative trends in the changing media environment, which undermines both the goals of democratically oriented media and the foundations of social-cultural development. This situation determines the need to analyze new patterns of audience behavior in connection with the development of the new media environment. The increasing effect of media dependence in the post-truth society has turned the new media into the main source of fakes, which is typical mainly for the American post-truth society. Based on the analysis of the traditional and new media, the authors show the ways to block the free dissemination of truthful information by the socalled “megaphone press”, serving as an advertising machine for politicians. The authors’ methodological approach to the study of the media environment is based on the principle of convergence of technologies and created and consumed content in the developing “post-truth society of the contemporary western type”. Convergence of the media environment, along with the positive trends, creates new opportunities and gives new impetus to the development of the post-truth society.